Study of polymorphism of toll like receptor-4 gene in crossbred cattleand its association with somatic cell count - SONWANE, S M; CHOPADE, M M; SAWANE, M P; YADAV, K N; PAWAR, V D; INGOLE, S D; KATKADE, B S (The Indian Journal of Animal Sciences, 2023)
The present study was undertaken to study the TLR4 gene polymorphism in exon 3 and its association with somatic cell count in HF×Gir cows using PCR-RFLP. Sixty crossbred cows (40 affected and 20 normal) between 3rd to 5th lactation were selected from Bombay Gowrakshak Mandali, Betegaon, Maharashtra. The confirmation of mastitis was done with the help of California Mastitis Test (CMT) and the blood samples of 40 affected animals were collected aseptically along with 20 normal animals. The mean of somatic cell score in normal cows ranged between 2.86 to 2.99 × 105 cells/ml, whereas for affected animal the range of somatic cell score was 3.45 to 5.72 × 105 cells/ml. The genomic DNA was isolated and exon 3 of TLR4 gene was successfully amplified by PCR using a specific primer. The PCR product was digested with HaeIII restriction enzyme. The PCR-RFLP of exon 3 with HaeIII enzyme revealed two genotypes ‘BB’ and ‘AB’ with band pattern 49 bp, 98 bp & 196 bp (BB) and 49 bp, 98 bp, 196 bp & 245 bp (AB), respectively. The mean of somatic cell score estimated for animals with genotypes ‘BB’ and ‘AB’ was 3.99±0.13 and 3.66±0.03, respectively. The two mean ‘t’ test analysis showed non-significant difference between somatic cell count with genotypes ‘BB’ and ‘AB’. It indicated that there was no association between the genotypes of exon 3 of TLR4 gene with somatic cell count in crossbred cows under present study.